Aerobic and sprint workouts for trained swimmers - Pyne, D. (2001)
One of the key considerations in training is to provide sufficient variation and stimulus for improvement. The two workouts examined here are taken from the training programs of Australian Swimming Team members at the peak of their season. These represent typical workouts undertaken by this level of swimmer and illustrate some features and variations that could be employed by any well-trained swimmer. For recreational and age group swimmers, the overall volume should be reduced by decreasing the number of efforts and distance of the different intervals used.